The Experience of Miners Relocated to Alternative Positions due to Silicosis in the Andean of CODELCO, Chile, 2010 - Diemen Delgado; Maria de los Angeles Aguilera; Fabian Delgado; Ani Rug (Elsevier, 2012)
Objectives: To understand the personal experiences of mine workers that have experienced job relocation due to silicosis at the Andina Division of Corporación Nacional del Cobre (CODELCO), Chile. The purpose of the study was to provide useful information for the development of new local, business and public policies for the care of workers with silicosis. Methods: A qualitative study based on a practical case study of 5 workers. The information was collected by means of structured individual interviews. The method of analysis was phenomenology. Results: The corporal axis was the most commented upon. It included awareness of the illness, body pains, fatigue, and antagonistic mood disorders (sadness, or the difficulty in finding meaning in life). As far as personal relationships, there was evidence of strong relationships with family, coworkers and friends, as well as extended family. Over all, the experience of relocation was positive with periods of impatience and uncertainty. The job reassignment provided a new and pleasant context for the relocated workers and in the process improved their perception of their quality of life. Conclusions: A multidisciplinary team should attend mine workers relocated because of silicosis by addressing the mental and physical aspects of their disease, along with the integral participation of close family members. It is suggested that this investigation be maintain over time to record the personal experiences in the medium-term, adding new cases with the intention of shedding more light on the phenomenon being studied. As a preventive measure, continual workshops are needed on the proper use of respiratory protection in addition, a group of monitors is required.